Comparison and impact of associated anomalies on the anal position index in neonates with anorectal malformation - Pitaka, Ririd Tri; Fauzi, Aditya Rifqi; Makhmudi, Akhmad; Gunadi, Gunadi (Springer Nature, 2022)
Objective: Some prognostic factors have affected the functional outcomes of patients with anorectal malformations (ARM) after definitive surgery, including the associated anomalies. Moreover, the anal position index (API) study in neonates from developing countries is minimal. We aimed to (1) compare the API between neonates with ARM and controls; and (2) determine the impact of associated anomalies on the API in neonates with ARM. Results: We ascertained 68 subjects: 35 neonates with ARM and 33 controls. The API of neonates with ARM was similar to controls, either male or female neonates (p = 0.51 and 0.90, respectively). Interestingly, the API in ARM males with associated anomalies (0.42 ± 0.07) was significantly lower than in control males (0.48 ± 0.02) (p = 0.005). Moreover, the API of ARM neonates with vertebral anomalies (0.35 ± 0.04) was lower than ARM neonates without vertebral anomalies (0.47 ± 0.07) (p = 0.021). In conclusion, associated anomalies and sex might affect the API in neonates with ARM. These findings should be considered and informed during counseling to the parents regarding the prognosis of functional outcomes in ARM neonates, particularly with associated anomalies.